German-Speaking Émigré Neuroscientists in North America after 1933: Critical Reflections on Emigration-Induced Scientific Change - Stahnisch, Frank W. (Österreichische Zeitschrift für Geschichtswissenschaften, 2010)
This paper endeavors to document and analyze the impact of forced-migration of German-speaking neuroscientists to Canada and the United States during the National-Socialist era, while specifically focusing on concepts and scientific applications of interdisciplinarity in 20th century neuroscientific research. The objectives of this paper are firstly, to describe the general research topic; secondly, to introduce a new model for the historiography and social studies of forced-migration in the neurosciences and thirdly, to explore, in a preliminary way, the impact that particular Central- European émigré-researchers had on this emerging postwar biomedical field in North America.